Sinonasal verrucous carcinoma with oral invasion - Karthikeya P (Indian Journal of Dental Research, 2006)
Verrucous carcinoma is a rare warty variant of squamous cell carcinoma, most often seen in the oral cavity and larynx. Its occurrence in the sinonasal tract is rare. This tumor constitutes approximately 1% of all sinonasal neoplasms. The clinical presentation and the histopathological features of verrucous carcinoma are a subject of continuous discussion amongst diagnosticians and pathologists. A case with oral and nasal presentation of this tumor is reported here.